EMPLOYMENT SOCIAL INSURANCE ARRANGEMENTS FOR ONLINE TRANSPORTATION DRIVERS BASED ON A PROGRESSIVE LEGAL PERSPECTIVE - Muhammad Ramdan; Indra Hafit Zahrulswendar (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
The presence of online transportation provides great benefits because it has created jobs to become online transportation drivers. However, there are many problems regarding online transportation drivers due to the lack of regulations governing them, one of which is regarding Social Insurance. This research is normative legal research, data collection technique is done by literature study, and data analysis is done by the descriptive method. The results of the study show that social insurance regulations for online transportation drivers need to be made immediately. This is important to be noticed by the government because online transportation drivers do not get the rights that workers get in the Manpower Act, one of which is the right to obtain social insurance. That is because the legal relationship between the online transportation application provider company and the online transportation driver is not classified as a